(untitled) (Jurnal Matematika, Statistika dan Komputasi, 2022)
The theory of frames which appeared in the last half of the century, has been generalized rapidly and various generalizations of frames in Hilbert spaces and Hilbert C^*-modules. In this paper, we will give some new properties of modular Riesz basis and modular g-Riesz basis that present a generalization of the results established in a Hilbert space.